Design of Augmented Reality Learning Media for Islamic Religious Education: Encouraging Religious Moderation in Junior High Schools - Ahmad Ta'rifin; Aisyah Zubaidah; Nurlaila Ana; Mohammad Yasin Abidin; Ulul Albab; Hani Hasnah Safitri (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to develop an Augmented Reality (AR)–based learning medium for Islamic Religious Education (IRE), integrating the concept of religious moderation in junior high schools. The initiative addresses the need for innovative, technology-driven educational tools that align with current pedagogical trends and religious values. The research employed a Research and Development (RD) approach using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. The AR learning media, named DOSIMA, was created as an Android application modeled on a modified Ludo game to deliver educational content through interactive images, videos, and web-based resources. The product was tested in three junior high schools with diverse characteristics: SMP Negeri 2 Kajen, SMP Negeri 1 Petungkriyono, and SMP NU Kesesi. Expert validation was conducted by media, content, and language specialists. Validation results confirmed the feasibility and appropriateness of the media. Field tests indicated a significant improvement in students’ cognitive abilities, with average test scores increasing from 71% to 89.5%. The N-gain score of 63.125% placed the product in the "Effective" category. The findings highlight the effectiveness of AR-based tools in enhancing religious education and promoting religious moderation. This challenges the prevailing notion that Islamic education is inherently traditional or non-technological. The study underscores the potential of integrating AR in religious education and offers a foundation for policy development to foster religious moderation in secondary education settings.